Absolute Impact Factor to Compare Journals and Research Publications of Different Subjects - Adhikari, Saumen (Journal of Information and Knowledge, 2019)
The paper explores the problem of the parameter, Impact Factor for analyzing research publications of different subjects. A new tool, Absolute Impact Factor is introduced as analytical solution to bring journals of all subjects in a scale.